Tarnished Plant Bug, Lygus lineolaris (Palisot de Beauvois) (Insecta: Heteroptera: Miridae) - Wayne N. Dixon; Thomas R. Fasulo (EDIS)
Lygus lineolaris (Palisot de Beauvois), the tarnished plant bug, attacks a wide variety of economically important herbaceous plants, vegetable crops, commercial flower plants, fruit trees, and nursery stock (Kelton 1975). In fact, over half of the cultivated plant species grown in the United States are listed as host plants for tarnished plant bugs (Capinera 2001). This document is EENY-245 (originally published as DPI Entomology Circular 320), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2001.